Factors Influencing Students Reading Comprehension Difficulties Amidst the Use of Modular Distance Learning Approach in Mindanao State University Sulu – Senior High School - Abbas, Khar-Diya A. (HM Publisher, 2021)
This research was conducted to determine the factors influencing students reading comprehension difficulties amidst the use of modular distance learning approach in Mindanao State University – Sulu Senior High School. It also aimed to understand reading comprehension and modular distance learning approach. It determines the reading comprehension difficulty level during modular distance learning approach as perceived by the students when they are classified in terms of strand. This study used mix – method. Data were gathered through the use of Focus Group Discussion and self-made survey questionnaire. Weighted mean and t-test were used. Purposive sampling design was utilized for the selection of the ten MSU – Sulu SHS Teachers and convenient sampling design was used for the selection of 25% population of MSU – Sulu SHS Students during the school year 2020 - 2021. The findings of this study revealed that reading comprehension is the ability of the students to analyze, decode, integrate prior knowledge, interpret and clearly understand the words, sentence, or compositions particularly the content and its contexts. The different strategies used in teaching reading comprehension as well as different strategies that can be used during the modular learning approach were presented. The emphasis on modular distance learning was found that it can be used as an alternative learning approach that uses self-learning modules. It was also revealed that both internal and external factors have influence students reading comprehension difficulties amidst the use of modular distance learning approach. Students’ perception on reading comprehension difficulty level during modular distance learning approach is difficult. There is no significant difference on students’ reading comprehension difficulty level amidst the use of modular distance learning approach as perceived by the students that resulted to the acceptance of the null hypothesis. The study recommended that the school administrators should initiate trainings, seminars and workshops about different strategies that is timely to help their faculty members improve the reading comprehension of the students. The school administrators should also supervise their teachers to use strategies that are appropriate and applicable on the type of learning style they are using. The teachers should use strategies and learning resources that suits the kind of learners and the type of learning style they have. The teachers should also exert extra effort in facilitating the students’ learning even in the absence of face-to-face interaction. The parents should guide and monitor their children’s learning at home.